The methylmercury-L-cysteine conjugate is a substrate for the L-type large neutral amino acid transporter, LAT1 - Yin, Z (2008)
Methylmercury (MeHg) is a potent neurotoxin. The mechanism(s) that governs MeHg transport across the blood-brain barrier (BBB) and other biological membranes remains unclear. This study addressed the role of the L-type large neutral amino acid transporter, LAT1, in MeHg transport. Studies were carried out in CHO-k1 cells. Overxpression of LAT1 in these cells was associated with enhanced uptake of [(14)C]-MeHg when treated with L-cysteine, but not with the D-cysteine conjugate. In the presence of excess L-methionine, a substrate for LAT1, L-cysteine-conjugated [(14)C]-MeHg uptake was significantly attenuated. Treatment of LAT-1 overexpressing CHO-k1 cells with L-cysteine-conjugated MeHg was also associated with increased leakage of lactate dehydrogenase (LDH) into the media as well as reduced cell viability measured by the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) reduction assay. In contrast, knock-down of LAT1 decreased the uptake of L-cysteine-conjugated MeHg and attenuated the effects of MeHg on LDH leakage and CHO-k1 cell viability. These results indicate that the MeHg-L-cysteine conjugate is a substrate for the neutral amino acid transporter, LAT1, which actively transports MeHg across membranes.